PEMANFAATAN APLIKASI CANVA SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS V SDN KETILENG 2 KOTA CILEGON - Aam aditia; Umaliahayati; Mohamad Bayi Tabrani (STKIP Subang, 2026)
The current era of globalization is considered very important, especially to improve the quality of education at the Elementary School (SD) level. Information and Communication Technology (ICT) has a crucial role in improving the quality of learning by utilizing various applications, one of which is Canva, which is a solution for electronic-based learning. Canva allows learning material creators to create interesting and interactive content.This research was conducted with the aim of implementing Canva as a learning media for Pancasila Education at SDN Ketileng 2 Cilegon City. The research method used is qualitative, which involves an in-depth description of the experiences and perceptions of learners and teachers towards the use of Canva in the learning process. The results showed that Canva is effective in increasing students' interest including Pancasila Education, by providing a more interactive and fun learning experience. The application of technology in education has great potential to create more inclusive and meaningful learning. This research underlines the importance of continuing to develop and strengthen the application of technology in education as a strategic step to prepare the younger generation to face the challenges of globalization and accelerating technological advances. Keywords: Utilization, Canva, Education, SDN Ketileng 2